Remote cerebellar hemorrhage after lumbar puncture in herpes simplex encephalitis. Issue 6 (22nd October 2015) - Nakata, Ruka; Motomura, Masakatsu; Morikawa, Minoru; Yoshimura, Toshiro; Kawakami, Atsushi
Abstract: Remote cerebellar hemorrhage is reported as a possible complication after supratentorial surgery and spinal surgery, and there is no previous report after lumbar puncture. A 44‐year‐old man was diagnosed with Herpes simplex virus (HSV) encephalitis, which was complicated with cerebellar hemorrhage remote from the active encephalitis lesion. The hematoma in the cerebellar hemisphere, shown as low a intensity lesion in a T2 star weighted angiography, image was diagnosed as a remote cerebellar hemorrhage caused by lumbar puncture. Physicians must be aware of this streaky, zebra‐pattern radiographic image of remote cerebellar hemorrhage.